Chapter Risorse e popolazione umana (Studi e saggi, 2020)
The history of the genus Homo, and of the sapiens species in particular, is different from that of other species due to the extreme importance of cultural evolution compared to biological evolution. But from the discovery of how to use fire and generate it, up to the invention of the steam engine, man essentially lives, like the other organisms of the biosphere, on the energy flow guaranteed by solar radiation. With the encounter between machines and fossil fuels and the entry into the era of engines, the rules of the game change radically, and the activities of Homo sapiens change in extent and intensity, in such a way as to progressively reduce the living space of all other animal and plant species, except for the allied and commensal ones. The global industrialized society arising from the meeting between machines and fossil sources is presently facing two fundamental difficulties: the gradual saturation of terrestrial ecosystems with the waste of social and economic metabolism, and the finiteness of fossil energy sources, which are not easy replacement due to their special chemical-physical properties.